An antibacterial non-woven fabric: preparation, antibacterial and mechanical properties. Issue 1 (27th July 2022) - Chen, Yamin; Wang, Hui; Yu, Yuanhao; Ning, Haoliang; Yuan, Sifan; Su, Shichao; He, Xiaohui; Xie, Jingpei; Peng, Shuge
Abstract: To improve the antibacterial properties of the non-woven fabric (Tel), the antibacterial Tel composed of chitosan and silver ions composite antibacterial agents (CS-Ag/Tel) was prepared by a facile impregnation method in this work. The morphology, surface composition, microstructure, stability and mechanical properties of the as-prepared antibacterial non-woven fabrics were characterized by FT-IR, SEM, ICP, contact angle and universal testing machine, respectively. The antibacterial performance was evaluated by agar diffusion method and viable bacteria counting method. The results showed that the chitosan-silver ions was successfully impregnated on the surface of the Tel, and endowed the Tel with good stability and antibacterial performance. The ICP test showed that the maximum release concentration of silver in CS-Ag/Tel was 0.142 ppm. The antibacterial tests showed the modified CS-Ag/Tel had an obvious inhibition zone and the antibacterial rate arrived at 96.33%. At the same time, the mechanical properties of the as-prepared CS-Ag/Tel was comparable to the raw Tel. These findings suggested that the as-prepared CS-Ag/Tel had an excellent antibacterial performance, which showed important value in the development and application of the non-woven fabric in the fields of cosmetics and medicine.